Analysis Of Co2 Storage in A Saline Aquifer Using A Fully Implicit Integrated Network Modeling Approach in the 'AZ' Field - Swadesi, Boni; Zayd, Ahmad; Buntoro, Aris; Kristanto, Dedi; Widiyaningsih, Indah; Lukmana, Allen Haryanto (UIR PRESS, 2025)
The increasing carbon dioxide (CO2) emissions from industrial and energy activities have driven the development of Carbon Capture and Storage (CCS) technology as a key solution for climate change mitigation. Among various geological storage options, saline aquifers offer significant advantages due to their large storage capacity, wide distribution, independence from hydrocarbon value, and stable geological and geochemical conditions. The “AZ” Field, located near a power plant emitting 2.2 million tons of CO2 annually, was selected as the study site for CO2 storage. This study aims to analyze the trapping mechanisms and optimize the CO2 storage capacity (storativity) using a fully implicit integrated modeling approach. The methodology involves building a static and dynamic model of the Johansen Formation saline aquifer, and integrating well and surface facility models using the well designer and network designer features in tNavigator. A 140-year simulation was conducted, comprising 40 years of injection and 100 years of post-injection period. Simulation results show that the “AZ” Field can store up to 83.9 Mt of CO2, predominantly through solubility/residual trapping mechanisms, in addition to structural trapping. No leakage was observed to the surface, indicating that caprock integrity remained intact throughout the simulation period. The fully implicit integrated modeling approach effectively captured the dynamic interactions between the reservoir, wells, and surface facilities, supporting the feasibility of the “AZ” Field as a safe and sustainable CO2 storage site.